312 In vivo electrophysiology sex differences in the locus coeruleus of wild type F344 rats - Rosaria J. Rae; Lori L. McMahon (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Women are twice as susceptible to ailments like anxiety, PTSD, and Alzheimer’s disease compared to men. The locus coeruleus (LC), the primary source of noradrenaline for the brain is implicated in these disorders, however physiological sex differences have never been assessed in the LC. METHODS/STUDY POPULATION: To address this gap, In vivo electrophysiology under anesthesia was used to measure single unit activity of noradrenergic LC firing patterns in 4-month-old wild-type Fischer male and female rats. Recordings measured neuronal activity under basal conditions and in response to a footshock stimulation which elicits burst firing in LC neurons. Single unit activity is sorted via automatic valley seeking scan PCA, additional manual sorting is done via line and template method. Analysis is done extracting interspike interval (ISI) and firing rate of single units, additional analysis is done to quantify properties of bursting patterns (burst duration, spikes per burst, interburst interval, etc…). RESULTS/ANTICIPATED RESULTS: This data shows that during LC burst firing, females have longer interspike intervals compared to males, supporting the inhibitory effect of E2 on LC firing. Additionally, females have significantly different waveform patterns than males, indicating possible differences in intrinsic properties, but further supporting sexually distinct physiology of the LC . Because female rats have been estrous cycle tracked via vaginal lavage, stratification into estrus groups and further analysis may uncover differences within females. These data suggest that estrogen acts as a potent neuromodulator of noradrenergic LC neurons, providing valuable insights into the physiology of this brain region. DISCUSSION/SIGNIFICANCE: This study is the first exploration of LC physiological sex differences. This work offers insights into a critical brain region implicated in many diseases, and may pave the way for future therapeutic approaches, particularly for women, who are at a higher risk of neurological disease developing.